Intranasal Lipid Nanoparticles for the Treatment of Neurodegenerative Diseases - Cunha, S.; Almeida, H.; Amaral, M.H.; Lobo, J.M. S.; Silva, A.C. (Current Pharmaceutical Design, 2017)
Background: Current treatments for neurodegenerative diseases are challenging, due to the absence of fully effective medicines. One of the major problems associated to these is the occurrence of non-targeting events, which leads to adverse effects and requires frequent dose administration. Methods: Researches have been performed to develop new drug delivery systems administrated by alternative routes. For example, the direct nose-to-brain delivery of drugs by means of lipid nanoparticles, such as solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), has been showing promising results. Results: Among the advantages of intranasal administration is the avoidance of passing the blood-brain barrier (BBB) to reach the central nervous system (CNS), allowing the direct delivery of drugs to the brain by a noninvasive way, minimizing systemic exposure and prolonging residence time. This review article discusses the advantages of using SLN and NLC for direct nose-to-brain drug delivery. A brief reference to other lipid-based carriers (liposomes, nanoemulsions and microemulsions) is also provided. Conclusion: The benefits of using SLN and NLC for improve nasal drug delivery have been demonstrated by in vitro, ex vivo and in vivo experiments. However, more in vivo animal studies are needed for advance to human clinical trials and reach clinics.
Keywords: microemulsions